2004
DOI: 10.1172/jci20935
|View full text |Cite
|
Sign up to set email alerts
|

Specific induction of neuronal cells from bone marrow stromal cells and application for autologous transplantation

Abstract: Bone marrow stromal cells (MSCs) have the capability under specific conditions of differentiating into various cell types such as osteocytes, chondrocytes, and adipocytes. Here we demonstrate a highly efficient and specific induction of cells with neuronal characteristics, without glial differentiation, from both rat and human MSCs using gene transfection with Notch intracellular domain (NICD) and subsequent treatment with bFGF, forskolin, and ciliary neurotrophic factor. MSCs expressed markers related to neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
300
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 297 publications
(313 citation statements)
references
References 36 publications
(12 reference statements)
8
300
1
3
Order By: Relevance
“…Mesenchymal stem cells in the bone marrow can differentiate to muscle (Ferrari et al, 1998;Dezawa et al, 2005), neural lineage cells (Kopen et al, 1999;Dezawa et al, 2004) and to various other cell types (Jiang et al, 2002). Another distinct population of bone marrow-derived stem cells can differentiate to cells of various lineages including muscle, endothelial, epithelial and neural cells (Yoon et al, 2005).…”
Section: Epigenetic Control Of Gene Expressionmentioning
confidence: 99%
“…Mesenchymal stem cells in the bone marrow can differentiate to muscle (Ferrari et al, 1998;Dezawa et al, 2005), neural lineage cells (Kopen et al, 1999;Dezawa et al, 2004) and to various other cell types (Jiang et al, 2002). Another distinct population of bone marrow-derived stem cells can differentiate to cells of various lineages including muscle, endothelial, epithelial and neural cells (Yoon et al, 2005).…”
Section: Epigenetic Control Of Gene Expressionmentioning
confidence: 99%
“…This because MSC cultures showed differentiation not only into the same mesodermal-lineage they belong but also into ectodermal-lineage, such as neural and epidermal cells, as well as into endodermal-lineage, such as hepatocytes and b cells. [1][2][3][4][5][6] However, efficiency of differentiation is usually not high, suggesting that this phenomenon is dependent on a small subpopulation. 7 Previously, we identified unique stem cells that we named multilineage-differentiating stress enduring (Muse) cells as one to several percent of the total MSCs of the bone marrow, adipose tissue and dermis.…”
Section: Introductionmentioning
confidence: 99%
“…Other types of stem cells, such as NSCs and progenitors from the embryonic ventral mesencephalon [64][65][66][67], adult NSCs from the subventricular zone [68], bone marrow stromal cells [69], and fibroblast-derived induced pluripotent stem (iPS) cells [61,[70][71][72] have also been used for this purpose. It has also been shown that human stem cell-derived DA neuroblasts, which will be required for patient application, can survive in animal models of PD and after maturation exert functional effects [54,58,66,69,71,72]. However, some properties that will be fundamental for successful clinical translation have not been demonstrated yet for human stem cell-derived DA neurons, including those that they can substantially reinnervate striatum, restore DA release in vivo, and markedly improve deficits resembling the symptoms experienced by patients with PD.…”
Section: Can Stem Cell-derived Neurons Replace Fetal Grafts In Pd Patmentioning
confidence: 99%